CASE STUDY: TATA NANO - Akanksha Verma; Abdularahman Alenezi; Abdelaziz Alkandari; Amira Amira (AIBPM Publisher, 2019)
The TATA NANO was a compact city car manufactured and marketed by Indian Automaker TATA MOTORS over a single generation, primarily in INDIA, as an inexpensive rear-engine hatchback intended to appeal to current riders of motorcycle and scooters. According to the recent, report INDIA overlook BRAZIL and become the sixth largest passenger vehicle producer in the world. This car is the cheapest car in the world than also people are not to buy this car for their level of status. There is various strategy which the company may apply wrong that why the car may not to be purchases more in the India.